KONSEP REWARD DAN PUNISHMENT MENURUT IRAWATI ISTADI (KAJIAN DALAM PERSPEKTIF PENDIDIKAN ISLAM) - Umi Baroroh (IAIN Purwokerto, 2018)
Abstract: This research was conducted to find out how reward and punishment according to Irawati certainly does not conflict with the value of Islamic education. This is a library research the data of which were taken from several works of Irawati Istadi and direct interviews with her. The researcher also took some data from several researchers who discussed Irawati Istadi's thoughts and from Islamic education figures whose thoughts had relevance to the research theme. Content analysis methods is applied to draw conclusions. From this research, it can be concluded that the concept of reward and punishment according to Irawati Istadi turns out to be compatible with the Islamic education. However, in Irawati's thought, there are also some differences shows the development of thoughts from previous figures of Islamic education and certainly did not conflict with the values of Islamic education. Keywords: reward, punishment, Islamic education, Irawati Istadi, educator.